Краснолаковая керамика в Черняховской культуре - Магомедов, Б.В.; Диденко, С.В. (Боспорские исследования, 2009)
The population of the Chernyakhov Culture (the second third of the 3rd - the first third of the 5th century AD) was mainly the Goths tribes. Most of the finds of Red slip ware on Chernyakhov’s sites came from the Black Sea coast and the Lower Danube. The wares from the Eastern zone of this territory have analogues mainly in the Crimea, and they form the «North Black Sea» series. The wares from Western zone have most of analogues from the provinces of the Lower Danube, and they were also produced there. They form the «West Black Sea» series. Therefore, the Chernyakhov market of imported table wares was divided into two spheres of influence. It can be explained not only by geographical closeness to the different economic centres of the Roman Empire, but also by division of the Goths into two branches (Terwingi-Visigoths and Greutungi-Ostrogoths). There was drastic increase of imported Roman goods to Chernyakhov settlements happened in the second third of the 4th century This fact might be an outcome of federated treaty between Constantine and the Goths in 332, which contained also the trade article.